PERANAN BAITUL MAAL WATTAMWIL (BMT) TERHADAP UPAYA PERBAIKAN MORAL MASYARAKAT DI KAWASAN DOLLY SURABAYA - Oktavia, Renny (An-Nisbah: Jurnal Ekonomi Syariah, 2014)
Implementation of Closing localization âDollyâ by Surabaya city government, followed by concrete steps by giving them the skills at the same time funding assistance for livelihood instead of pimps and prostitutes, is the appropriate steps to address the socio-economic problems that occur in the region.Â  In order to preserve government capital, it needs to connect them with Sharia Microfnance Institutions (LKMS), the Baitul Maal Wattamwil (BMT). BMTÂ  will then be able to assist to increase the capacity of their business in the form of additional capital. In addition, through mentoring activities or coaching, BMT make efforts to maximize the role of the moral improvement of society, such efforts include: 1) mentoring activities of the economy or business and 2) mentoring activities of the Islamic valuesÂ Â Â  or Ruhiyah. Keywords: Government, BMT, Capital, Coaching, Morality Improvement